3.8k views
3 votes
Evaluate the expression when m= -6
m²+5m-1​

2 Answers

3 votes

Answer:


\huge\boxed{\bf\:5}

Explanation:

Expression =
m^(2) + 5m - 1.

They've given the value of m as - 6.

Then, by substituting - 6 in place of 'm' in the equation,


m^(2) + 5m - 1\\= (-6)^(2) + 5(-6) - 1\\= 36 - 30 - 1\\= \boxed{\bf\:5}


\rule{150pt}{2pt}

User Mattjvincent
by
5.4k points
6 votes

Answer:

When m = -6, then we have:

m² + 5m - 4

Explanation:

(-6)² + 5 x (-6) - 4

36 - 30 + 4

36 - 34

2

User Pratik Deoghare
by
5.3k points